Quantitative Measurement of Osseous Pathology in Advanced Glenohumeral Osteoarthritis. (6th September 2017) - Iannotti, Joseph P.; Jun, Bong-Jae; Patterson, Thomas E.; Ricchetti, Eric T.
Abstract : Background: Osteoarthritis of the glenohumeral joint has typical patterns of deformity as described by Walch et al. However, more severe glenoid pathology may be difficult to classify. The purpose of this study was to use 3-dimensional computed tomography (3-D CT) imaging analysis to define common pathologic subtypes that can be differentiated from the current Walch classification. Methods: We performed quantitative measurements of premorbid and pathologic anatomy using preoperative 3-D CT scans from 155 cases of advanced glenohumeral osteoarthritis that underwent anatomic or reverse total shoulder arthroplasty. We defined premorbid glenohumeral anatomy on the basis of previously validated methods using 3-D glenoid vault and humeral best-fit circle models including the premorbid glenoid version, joint-line medialization, and humeral-glenoid alignment (HGA). We determined the anatomic features that differentiate new glenoid morphologic subtypes from the existing Walch classification both qualitatively and quantitatively. Results: We defined 2 new glenoid subtypes (B3 and C2) for which the glenoid pathology and humeral alignment were not defined in the original Walch classification. The B3 glenoid has high pathologic retroversion, normal premorbid version, and acquired central and posterior bone loss that, on average, is greater than that of the B2 glenoid. The C2 glenoid is dysplastic with high pathologic retroversion, high premorbid version, and acquired posterior bone loss, giving it the appearance of a biconcave glenoid with posterior translation of the humeral head. This C2 glenoid can be confused with the B2 glenoid. Conclusions: The B3 and C2 patterns have qualitative and quantitative differences that may result in different clinical outcomes than classic B2 or C types; therefore, our findings suggest that these new subtypes should be included in a new or modified classification system.